2022
DOI: 10.3389/fpsyg.2022.817298
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience, Cardiovascular Disease, and Metabolic Disturbances: A Systematic Review

Abstract: BackgroundPositive psychosocial factors can play an important role in the development of cardiovascular disease (CVD). Among them, psychological resilience (PR) is defined as the capacity of responding positively to stressful events. Our aim was to assess whether PR is associated with CVD or metabolic disturbances through a systematic review.MethodsWe gathered articles from PubMed, Web of Science, PsycInfo, and Google Scholar up to October 28, 2021. We included articles that were in English, were observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Psychological well‐being is of high importance in individuals with MI, given the clear links between stress, depression, and adverse CVD outcomes. 29 , 30 , 31 In this prospective study of psychological recovery in a diverse group of women with MI, LR was associated with poorer psychological recovery over time. Women with LR reported greater perceived stress and depressive symptoms scores than those with HR throughout the first 2 months post MI, even though PSS‐4 and PHQ‐2 scores decreased overall.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Psychological well‐being is of high importance in individuals with MI, given the clear links between stress, depression, and adverse CVD outcomes. 29 , 30 , 31 In this prospective study of psychological recovery in a diverse group of women with MI, LR was associated with poorer psychological recovery over time. Women with LR reported greater perceived stress and depressive symptoms scores than those with HR throughout the first 2 months post MI, even though PSS‐4 and PHQ‐2 scores decreased overall.…”
Section: Discussionmentioning
confidence: 83%
“…Although it is possible that resilience could result in better cardiovascular outcomes, studies to date have been equivocal. One systematic review noted associations between HR with lower risk of cardiovascular events and slower progression of CVD risk factors such as hypertension and diabetes, 29 but other studies have not found such associations. 14 This may be due in part to the inherent limitation of subjective measures used to characterize resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Відомо, що після менопаузи естрогенний захист швидко зникає, а наявність некоригованих факторів ризику різко підвищує ймовірність серцево-судинних ускладнень у цей віковий період. Існування ілюзії жіночої захищеності, яка полягає в тому, що серцевосудинні захворювання розвиваються у жінок на десятиліття пізніше, ніж у чоловіків, може ввести в оману клініциста просто на підставі гендерної приналежності, що призведе до відстроченого надання допомоги таким пацієнткам [20,21].…”
Section: метаболічний синдром і його вплив на здоров'я жінкиunclassified
“… 7 In the resilience literature broadly, higher levels of resilience have been associated with decreased levels of perceived stress in relation to daily stressors and may have a protective association with cardiovascular diseases and metabolic disturbances. 8 The implementation of interventions which enhance resilience may be beneficial in reducing stress levels and reducing morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%